Synthesis and Wetting Behavior of Polyurethanes Containing Polyoxetane Soft Blocks with Semifluorinated and Bromomethyl Side Chains - 黄继庆 王君 孟卫东 卿凤翎 (Dong Hua da xue xue bao. Zi ran ke xue ban., 2010)
Polyoxetanes bearing short fluorinated and/or bromomethyl pendant groups were prepared from 3,3-bis（2,2,2-trifluoroethoxymethyl）oxetane and/or 3,3-bisbromomethyloxetane by ring-opening polymerization.A series of novel polyurethanes（PUs）containing polyoxetanes as soft blocks was synthesized by the reaction of polyoxetanes,isophorone diisocyanate（IPDI）,and 1,4-butanediol（BD）.The thermal properties and wetting behavior of these novel polymers were evaluated using TGA,DSC and contact angle analysis.The cotton fabrics treated with PU3 showed good hydrophobic property,and its contact angle for water was 133°.